A Test of Miller and Modigliani Dividend Policy Irrelevance Theory in Nigerian Stock Market - Philomina I, Udobi; Wilfred I., Iyiegbuniwe (American Finance & Banking Review, 2018)
This study empirically tests for the validity of Miller and Modigliani’s dividend irrelevance proposition in the Nigerian Stock Exchange (NSE). Secondary data were obtained from the Nigerian Stock Exchange fact book and firms’ annual audited financial statements for fifteen years (2001-2015). Mediation Analyses, was used to measure the direct and indirect effects of dividend on stock price. Correction of the anomalous use of current dividend and current earnings by the use of naive expectation of dividend and earnings revealed that the direct effect of expected dividend on share price is significant but the indirect effect of expected dividend on share price through earnings is not significant. The implication of these results is that expected dividend has its unique (direct) effect on share price beyond the effect on share price which it shares with expected earnings (indirect effect). This conclusion suggests that dividend policy is relevant in valuation of shares in NSE. It was therefore recommended that company management should treat dividend as an active corporate finance decision-making variable and should employ dividend in information signalling to capital market investors.